PERAN AGILE LEADERSHIP DAN STRATEGIC AGILITY PLANNING DALAM PENINGKATAN KINERJA UMKM PROVINSI PAPUA BARAT INDONESIA - Arizqi Arizqi; Diah Ayu Kusumawati (AdBispreneur : Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2023)
Micro, Small and Medium Enterprises (SMEs) have a strategic role in improving the National Economy. For this reason, it is necessary to contribute various parties in efforts to improve the performance of SMEs. This study aims to develop a model related to improving SME's performance through agile leadership and strategic agility planning. The sample of this study was 200 MSMEs in West Papua Province. Analysis of research data was carried out by testing structural equational modeling (SEM) and using a variance approach (partial least square). The results show that agile leadership is able to increase the readiness to change of SMEs in West Papua Province, but readiness to change itself has not been able to improve the performance of SMEs in West Papua Province. Agile leadership has not been able to improve or create workforce transformation for MSMEs in West Papua Province. The implementation of Strategic agility planning is able to increase readiness to change (readiness to change) and can also create workforce transformation (workforce transformation) in MSMEs in West Papua Province. Furthermore, workforce transformation is able to improve the performance of MSMEs in West Papua Province.Usaha Mikro Kecil dan Menengah (UMKM) memiliki peran yang strategis dalam meningkatkan Perekonomian Nasional. Untuk itu diperlukan kontribusi berbagai pihak dalam upaya peningkatan kinerja UKM. Penelitian ini bertujuan mengembangkan sebuah model terkait peningkatan kinerja SME’s melalui agile leadership dan juga strategic agility planning. Sampel dari penelitian ini adalah 200 UMKM di Provinsi Papua Barat. Analisis data penelitian dilakukan dengan pengujian Structural Equational Modelling (SEM) dan menggunakan pendekatan varians (partial least square). Hasil menunjukkan bahwa agile leadership mampu meningkatkan readiness to change pada UMKM di Provinsi Papua Barat, akan tetapi readiness to change sendiri nyatanya belum mampu meningkatkan kinerja UMKM di Provinsi Papua Barat. Agile leadership belum mampu meningkatkan atau menciptakan workforce transformation pada UMKM di Provinsi Papua Barat. Penerapan strategic agility planning mampu meningkatkan kesiapan untuk berubah (readiness to change) dan juga dapat menciptakan transformasi tenaga kerja (workforce transformation) pada UMKM di Provinsi Papua Barat. Selanjutnya workforce transformation mampu meningkatkan kinerja UMKM di Provinsi Papua Barat.